Endotracheal tube placement with fibre optic sensing - Gadsby, Brett (2023)
Unrecognised oesophageal intubation is often described as a ‘Never Event’; an entirely preventable and extremely serious incident. However, there is still prevalence, with severe consequences for the patient. The current gold standards of visually confirming passage through the vocal cords, observing chest movement, and end-tidal capnography all have limitations. There is an opportunity for an alternative method to determine the correct endotracheal tube placement in the trachea. One such solution is described here, through the development of a compact fibre optic sensor integrated into a standard endotracheal tube. The sensor contains no electrical components inside the invasive portion of the device, and it is magnetic resonance imaging safe.